Myopia and time spent for indoor and outdoor activities among first year undergraduate students in UiTM Puncak Alam / Muhammad Nasa’i Mohd Nawawi - Mohd Nawawi, Muhammad Nasa’i (2016)
Purpose: This study was conducted to determine whether light exposure, near work and genetic has influence on myopia progression. Method: A set of questionnaires was distributed among first year undergraduate in UiTM Puncak Alam and has successfully gathered 200 data. The data was analysed using descriptive analysis, cross-tabulation analysis and correlation analysis. Results: More exposure to light seems to cause less myopia. Students who spent a lot of time using computers, phone and other electronic devices are more myopic. The results showed that genetic (parental myopia) play a role in the development of myopia among students. Mothers give most contribution in the development of myopia. Conclusion: As a conclusion, more exposure to light seems to be associated with less myopic and longer duration doing near work activities will increase development of myopia. Parental myopia also can contribute development of myopia.